PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KESADARAN LINGKUNGAN SISWA KELAS IV SDN 1 BANGSRI PADA PEMBELAJARAN IPAS TOPIK LINGKUNGAN - Marsela, Putri; Imro’athush Sholihah, Husna; Farih Kurniawan, Wildan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This aimed to improve environmental awareness and learning outcomes of fourth grade students at SDN Bangsri through the implementation of the Project Based Learning (PjBL) model in science and social studies (IPAS) learning. These results show that two cycles of Classroom Action Research (CAR) were used in this study. These results show that two cycles of Classroom Action Research (CAR) were used in this study. Ten male and five female fourth-graders made up the study's subjects. Techniques for gathering data using observation sheets, questionnaires, documentation, and evaluation tests. The learning project carried out was planting green beans using used plastic cups as a form of environmental care and reuse of waste materials. The findings demonstrated that the implementation of the Project Based Learning (PjBL) model was able to improve students’ environmental awareness and learning outcomes. Environmental awareness completeness increased from 60% in the pre-cycle to 73.33% in Cycle I and increased again to 86.67% in Cycle II. Learning outcomes also improved from 60% completeness in Cycle I to 86.67% in Cycle II. Student learning activities increased from an average score of 73 in Cycle I to 84 in Cycle II. Therefore, the Project Based Learning (PjBL) model can improve environmental awareness and learning outcomes of fourth grade students in IPAS learning.